The Role and Impact of Letters of Recommendation (LOR) in University Admissions and Career Advancement: Challenges and Prospects - Takhsinovna, Nasretdinova Makhzuna; Hakim oʻg'li, Bekpo‘latov Muxiddin (Journal of Science in Medicine and Life, 2025)
Letters of Recommendation (LORs) serve as critical qualitative assessments in university admissions and professional hiring processes. They offer insights into applicants' personal qualities, leadership potential, and professional behavior, supplementing quantitative metrics. This comprehensive study analyzes the significance of LORs, highlights challenges such as subjectivity, implicit bias, and lack of standardization, and examines innovative reforms aimed at enhancing fairness and reliability. The findings underscore the necessity for structured templates, recommender training, and integration of technology to mitigate bias and improve decision accuracy. The paper concludes with recommendations to optimize LOR use in diverse cultural and institutional contexts.